EDUKASI KESEHATAN MENTAL UNTUK MENINGKATKAN PENGETAHUAN SISWA SMA: STUDI PENYULUHAN “MENTAL HEALTH IS THE REAL GLOW UP” - Sukma, Bagja Angga; Deasy, Afrieani; Salmiyah, Emy; Megasari, Mona; Risnawati, Risnawati; Nurjanah, Intan (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Mental health constitutes a crucial component of adolescent development; however, many students continue to demonstrate limited knowledge regarding the identification of stress, anxiety, and appropriate emotional management strategies. The educational program titled “Mental Health is The Real Glow Up” was held at SMAN 1 Cililin on October 13, 2025, with the objective of enhancing students’ comprehension and awareness of mental health. This study utilized a quantitative descriptive design with a pre-test and post-test approach. A total of 100 students participated in the activity. Evaluation findings revealed a notable improvement in students’ knowledge: prior to the intervention, most students fell into the moderate (47%) and poor (40%) knowledge categories, whereas following the intervention, the majority shifted to the good (47%) and moderate (53%) categories. The program demonstrated its effectiveness in increasing students’ mental health literacy and is recommended for adoption as a routine school initiative to further strengthen mental health awareness among adolescents.